Does the saltatory pattern on cardiotocograph (CTG) trace really exist? The ZigZag pattern as an alternative definition and its correlation with perinatal outcomes. (2nd November 2021) - Gracia-Perez-Bonfils, Anna; Vigneswaran, Kugajeevan; Cuadras, Daniel; Chandraharan, Edwin
Abstract: Background: The saltatory pattern (SP) has been defined by guidelines as a uniformly increased bandwidth of >25 beats per min lasting for 30 min. However, previous research suggest that it is very unusual to observe such a "uniform" increase in the bandwidth persisting for >30 min. Baseline fetal heart rate variability (FHRV) on cardiotocography reflects the integrity of the central nervous system. During labor, in the presence of a gradually-evolving hypoxia associated with the onset of metabolic acidosis, FHRV may be reduced. However, if a fetus is exposed to rapidly-evolving hypoxia, it may not have sufficient time to release catecholamines and the perfusion of central organs can be impaired. In such cases, simultaneous increased activity of the sympathetic nervous system to obtain more oxygen as well as enhanced parasympathetic activity to reduce the myocardial workload can lead to autonomic instability. This exaggerated autonomic response can be seen frequently on the cardiotocograph as a rapid, irregular, abrupt "up and down" fluctuation across the baseline (amplitude >25 beats per min). The authors have termed this pattern as "ZigZag" when apparent for a minimum of 1 min. It differs from the SP in terms of duration and uniformity of the bandwidth. Objective: To determine the incidence of the SP during labor as well as a shorter and less uniform version of the SP newly called "ZigZag pattern" (ZZP). The intention was to correlate them with perinatal outcomes, taking into account the duration of the ZZP. Study design: A retrospective analysis of 500 consecutive cardiotocograph traces was performed to identify saltatory patterns and ZigZag patterns of 1 and 2 min of duration. Apgar scores, umbilical cord pH values and admission to the Neonatal Unit were evaluated and correlated with the cardiotocograph findings. Results: Not a single case of the SP was observed. A ZZP of 1 min of duration (ZZP1) was identified in 30.1% of the CTG during the last hour prior to delivery; ZZP lasting for 2 min (ZZP2) were identified in 8.9% of cases during the same period. Apgar scores at 1 min of ≤7 were significantly more frequent in newborns where the ZZP was observed (36.7% in ZZP1 and 54.5% in ZZP2 versus 9.5% in fetuses without); similarly, the Apgar scores at 5 min of ≤7 were also more frequent when ZZP was observed (6.7% in ZZP1 and 13.6% in ZZP2 versus 1.1% in controls). Moderate acidosis (pH 7.0–7.10) was more common in fetuses with the ZZP (14.3% in ZZP1 and 15% in ZZP2) compared to those without (4.6 and 7.2%, respectively). Similarly, mild acidosis (pH 7.1–7.2) was more common with the ZZP (40.3% in ZZP1 and 35% in ZZP2 versus 27.6 and 31.7%, respectively without ZZP). The neonatal admission rate was significantly higher in fetuses with the ZZP (8.7% in ZZP1 and 11.4% in ZZP2 versus 1.1% in controls). Conclusions: In line with previous research, our study suggest that SP is an almost nonexistent phenomenon. Alternatively, the ZigZag pattern (ZZP) has been defined as an exaggerated, irregular, "up and down" fluctuation of the baseline variability with an amplitude of >25 beats per min, lasting for 1 min or longer. It represents autonomic instability during human labor and it differs from the SP in terms of uniformity and length. Newborns with a ZZP during active maternal pushing were found to have statistically-significant lower Apgar scores at the 1st and 5th min, moderate and mild acidosis in the umbilical artery and an 8.7–11.4-fold higher neonatal admission rate. Clinicians should stop oxytocin infusion and/or active maternal pushing to improve fetal oxygenation if the ZZP is observed.